2005
DOI: 10.1093/bja/aei024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing on the response to postal questionnaires concerning satisfaction with anaesthesia care † ‡

Abstract: The response rate is significantly lower at 9 weeks compared with 1 and 5 weeks after discharge. The total mean problem score remains unchanged but certain fields show fewer problems after 9 weeks compared with 1 and 5 weeks. Questionnaires on patient satisfaction with anaesthesia care should be sent within 5 weeks of discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…The current study standardized the data-collection mode and found a significant association between survey time and patient-reported experiences for three of the six scales. This is in line with the aforementioned studies, but contradicts another study from Switzerland in which the data-collection mode was also standardized [12]. However, the Swiss study only included one hospital, a specific patient group and a relatively small sample.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The current study standardized the data-collection mode and found a significant association between survey time and patient-reported experiences for three of the six scales. This is in line with the aforementioned studies, but contradicts another study from Switzerland in which the data-collection mode was also standardized [12]. However, the Swiss study only included one hospital, a specific patient group and a relatively small sample.…”
Section: Discussionsupporting
confidence: 58%
“…However, a closer investigation of these studies shows that in all except one [11], the data collection mode changed between the different measurements; the aforementioned timing effects might therefore have been due to changes in data collection mode. In fact, the best-designed study concerning the association between survey timing and patient satisfaction found little association between survey timing and patient satisfaction measures [12]. That study grouped patients into three different mailing intervals: 1, 5 and 9 weeks after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…All responses received were included in the analysis, as it has previously been demonstrated that recall bias was not a significant issue. 21 …”
Section: Questionnaire Administrationmentioning
confidence: 99%
“…Increasing length of time between intervention and postal survey has been shown to reduce questionnaire response rates. 5 We may now confidently counsel our strabismus patients preoperatively that the expected duration of conjunctival redness following surgery is approximately 10 weeks. More specifically, by the fifth postoperative week, approximately 25% of patients find that their operated eye is back to its preoperative color.…”
Section: Discussionmentioning
confidence: 97%